Online self-test identifies women at high familial breast cancer risk in population-based breast cancer screening without inducing anxiety or distress. (June 2017) - van Erkelens, A.; Sie, A.S.; Manders, P.; Visser, A.; Duijm, L.E.; Mann, R.M.; ten Voorde, M.; Kroeze, H.; Prins, J.B.; Hoogerbrugge, N.
Abstract: Introduction: Identifying high familial breast cancer (FBC) risk improves detection of yet unknown BRCA1/2-mutation carriers, for whom BC risk is both highly likely and potentially preventable. We assessed whether a new online self-test could identify women at high FBC risk in population-based BC screening without inducing anxiety or distress. Methods: After their visit for screening mammography, women were invited by email to take an online self-test for identifying highly increased FBC risk-based on Dutch guidelines. Exclusion criteria were previously diagnosed as increased FBC risk or a personal history of BC. Anxiety (State-Trait Anxiety Inventory Dutch Version), distress (Hospital Anxiety Depression Scale) and BC risk perception were assessed using questionnaires, which were completed immediately before and after taking the online self-test and 2 weeks later. Results: Of the 562 women invited by email, 406 (72%) completed the online self-test while 304 also completed questionnaires (response rate 54%). After exclusion criteria, 287 (51%) were included for data analysis. Median age was 56 years (range 50–74). A high or moderate FBC risk was identified in 12 (4%) and three (1%) women, respectively. After completion of the online self-test, anxiety and BC risk perception were decreased while distress scores remained unchanged. Levels were below clinical relevance. Most women (85%) would recommend the self-test; few (3%) would not. Conclusion: The online self-test identified previously unknown women at high FBC risk (4%), who may carry a BRCA1/2-mutation, without inducing anxiety or distress. We therefore recommend offering this self-test to women who attend population-based screening mammography for the first time. Highlights: Familial breast cancer risk was self-assessed in population-based breast cancer screening. About 4% of women have high risk and are potential candidates for BRCA1/2 genetic testing. Self-assessment of familial breast cancer risk did not induce anxiety or distress. Therefore the online self-test may be added to population-based breast cancer screening. An online referral test version is available atwww.erfelijkekanker.nl/test .